Yield and seed chemical composition of Lupinus mutabilis in Portugal - Martins,João Manuel Neves (2016)
Lupinus mutabilis Sweet (tarwi), being cultivated for thousands of years in the Andean region, is regarded as a potential crop for Europe, especially because of its high protein and oil content. The objective of this study was to revise the productivity and seed composition analyses of several tarwi accessions conducted over several years, in a Mediterranean environment (Lisbon, Portugal), in order to select more suitable lines. The productivity, although low (bellow 2 t/ha, in average), and variable (ranging from 0.26 to 6.0 t/ha), indicates that it should be possible to obtain lines with productivity levels high enough to make of this species a non-irrigated autumn-sown legume crop. These results are more encouraging when compared with the lower yields obtained in central Europe, where indeterminate growth also often causes unsurpassed difficulties. The chemical composition of tarwi seeds obtained in this Mediterranean environment reaches very high levels both in the protein content (up to 50%) and in oil (up to 19%). It is possible to select plants for higher oil levels with little reduction on the protein content. Seeds seem to have a slightly lower protein content than when obtained under central European conditions, but with oil contents consistently higher. Presently, the main obstacles to be transposed in order to make tarwi a crop for the Mediterranean area are: to increase cold and frost tolerance, in order to adapt it to colder winters than those in coastal areas; to increase seed yield and oil content (without reducing protein); to increase resistance to pests and diseases and a better competition against weeds; and to optimise the plant architecture in order to maximise pod and seed set without compromising productive flexibility (so much necessary to face the typical Mediterranean climate interanual variability).